2023
DOI: 10.1021/acsami.2c22762
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Thermal Protection Polymeric Materials with Self-Sensing and Self-Adaptation Deformation Abilities

Abstract: Based on the strategy of killing two birds with one stone, we introduce thermally expandable microspheres into a silicone rubber matrix to fabricate temperature-responsive controllable deformation materials, which exhibit intelligent deformation properties as well as enhanced thermal protection performance, for dynamic thermal protection in the next-generation morphing aircrafts. The formation of hollow structures endows the material with intelligent thermal management ability and makes the thermal conductivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…As shown in Figure b, the microspheres in the active layer were subjected to intense thermal expansion, resulting in a rapid increase in the longitudinal expansion ratio in the first 66 s, and then tended to stabilize when the internal and external pressures of the microspheres reached equilibrium, whereas the transverse deformation was significantly suppressed under the constraint of the passive layer, and the expansion ratio was significantly reduced (Slope L > Slope T ) and remained stable for 277 s. The expansion behavior of the material is driven by expandable microspheres, which are uniformly dispersed in the rubber matrix. As the previous research indicated, when exposed to heat, the low-boiling-point solvent inside the microspheres increases the internal pressure through phase transition, the heating temperature exceeds the glass transition temperature of the shell, and the microspheres expand driven by the internal pressure. Under elastic force binding of the cross-linked network of the rubber matrix, the material expands to the maximum value when the expansion force is balanced with the binding force to avoid rupture.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure b, the microspheres in the active layer were subjected to intense thermal expansion, resulting in a rapid increase in the longitudinal expansion ratio in the first 66 s, and then tended to stabilize when the internal and external pressures of the microspheres reached equilibrium, whereas the transverse deformation was significantly suppressed under the constraint of the passive layer, and the expansion ratio was significantly reduced (Slope L > Slope T ) and remained stable for 277 s. The expansion behavior of the material is driven by expandable microspheres, which are uniformly dispersed in the rubber matrix. As the previous research indicated, when exposed to heat, the low-boiling-point solvent inside the microspheres increases the internal pressure through phase transition, the heating temperature exceeds the glass transition temperature of the shell, and the microspheres expand driven by the internal pressure. Under elastic force binding of the cross-linked network of the rubber matrix, the material expands to the maximum value when the expansion force is balanced with the binding force to avoid rupture.…”
Section: Resultsmentioning
confidence: 99%
“…Biocompatibility refers to the ability of a material to interact with biological systems without causing harmful effects. [16] Studies have shown that PEMA and its composites exhibit low cytotoxicity and good biocompatibility with human cells. PEMA also has a low inflammatory response, which is an essential characteristic for materials used in biomedical applications.…”
Section: Various Applications Of Polyethyl Methacrylate (Pema)mentioning
confidence: 99%
“…PEMA composites have excellent fatigue resistance and high-temperature capabilities, making them an ideal choice for aircraft structures, engine components, and other aerospace applications . [16] Automotive: Lightweight materials are becoming increasingly important in the automotive industry due to their potential to improve fuel efficiency and reduce emissions. PEMA composites could be used to manufacture lightweight body parts, such as hoods, fenders, and doors, which would improve the overall fuel efficiency of vehicles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 16–19 ] In recent years, utilizing TEMs to prepare CPCs has garnered significant interest from the scholarly community. [ 20–27 ] Cai et al. obtained the tunable EMI shielding in polydimethylsiloxane (PMDS)/TEMs/carbon nanotube (CNT) composites.…”
Section: Introductionmentioning
confidence: 99%